Epidemiology of hepatitis B‐associated hepatocellular carcinoma in Victoria. Issue 5 (14th May 2013) - Sinclair, M.; Roberts, S.; Kemp, W.; Knight, V.; Dev, A.; Gow, P.; Philpott, H.; Kronborg, I.; Arachchi, N. J.; Bell, S.; Lim, L.; Gorelik, A.; et al.
Abstract Background Chronic hepatitis B (HBV) and cirrhosis are major risk factors for hepatocellular carcinoma (HCC). The proportion and characteristics of cases with cirrhosis are not well documented. Aim Our aim was to compare demographic, viral and tumour characteristics of HBV‐associated HCC in an Australian cohort, in patients with and without cirrhosis. Methods Existing HCC databases at six Melbourne teaching hospitals were reviewed for cases associated with HBV. Patient demographics, HBV viral characteristics, presence of cirrhosis, serum alpha‐fetoprotein and tumour size were assessed. Mode of diagnosis was recorded through surveillance or symptoms, and treatment was either palliative, percutaneous or surgical. Results We identified 197 cases of HBV‐related HCC. The mean age was 57.9 ± 12.9 years; 83% were male, and 55.3% and 35.3% were of Asian and European descent respectively. Of 168 patient with available data, 146 (87%) had cirrhosis versus 22 (13%) without. Patients with cirrhosis tended to be older (median 60 vs 52 years, P = 0.078). Asian patients were more likely to have HCC without cirrhosis than Europeans (17% vs 6%, P = 0.04). There were no other differences identified between cirrhotic and non‐cirrhotic patients. Thirty‐four per cent of patients had tumours greater than 5 cm at diagnosis, and 47% were diagnosed after presenting with symptoms. Twelve patients with HBV‐HCC were outside current screening guidelines. Conclusion Most patients in Melbourne with HBV‐associated HCC have cirrhosis. HCC characteristics in non‐cirrhotic and cirrhotic patients were similar. The large number of patients detected through symptoms and with large tumours reinforces the need for vigilance in screening.